Cost-minimisation Analysis from a Non-inferiority Trial of Ready-Made versus Custom-Made Spectacles for School Children in India. (3rd September 2021) - Minakaran, Neda; Morjaria, Priya; Frick, Kevin D.; Gilbert, Clare
ABSTRACT: Purpose: Uncorrected refractive error is the leading cause of visual impairment in children. Many countries, including India, implement school eye health programmes involving vision screening and provision of free spectacles. This is costly for governments/organisations involved. This analysis estimates potential cost-savings if ready-made spectacles, in addition to traditional custom-made spectacles, are available for dispensing in school eye health programmes. Methods: An economic evaluation was conducted alongside a randomised controlled trial comparing spectacle wear of ready-made spectacles versus custom-made spectacles for children aged 11–15 years in schools in India. A cost-minimisation approach was used to calculate cost-savings of a 'ready-made spectacles available' programme compared with a 'custom-made spectacles only' school programme. The analysis was from a service provider perspective. Main outcomes: cost-saving per child needing spectacles and cost-saving per 1000 children screened. Results: The prevalence of uncorrected refractive error was 2.23%, and 86% of children were eligible for ready-made spectacles. The cost per child needing spectacles in a custom-made spectacles only programme was USD$26.91, and in a ready-made spectacles available programme was $11.15, producing a 58.6% cost-saving per child needing spectacles of $15.76. Considering the total cost of the eye health programme, this equated to a 15.1% cost-saving per 1000 children screened of $361. Results were robust to multivariate sensitivity analyses. Conclusion: Our study is the first to demonstrate the significant cost-saving potential of ready-made spectacles in school eye health programmes for uncorrected refractive error compared with custom-made spectacles alone. This has substantial economic benefits for national/international programmes.